Requency of Over Weight and Obesity and its Determinants Among Adult Population of District Swat Khyber Pakhtunkhwa Pakistan - Naeemullah, Nadia Khan, Muhammad Jibran Khan, Anwar Khan Wazir, Arif Iqbal, Muhammad Ishtiaq, Said Akbar Khan, Jawad Ali (Pakistan Journal of Medical & Health Sciences, 2022)
Background: In both emerging and wealthy nations, the epidemic of overweight and obesity has exploded in the last several decades, becoming a huge public health concern. Objective: To estimate the frequency of overweight and obesity and its important determinants among the adult population of Selected Districts of Khyber Pakhtunkhwa Pakistan Methods: A descriptive cross sectional study was conducted by the Department of Community Medicine, Saidu Medical College, Swat Khyber Pakhtunkhwa Pakistan; from January to April 2022. A total of 410 adults were selected and a structured questionnaire was used to collect relevant information. Results: Results showed that 67.07% had age above 30 years; 72.44% were males, 37.32% were illiterate; 51.95% had monthly income less than 25000/ PKR; 54.39% were married; and 26.34% had family history of overweight and obesity. Moreover, 52.93% had sedentary life; 37.56% watch television; and 15.85% & 17.80% had diabetes mellitus & hypertension respectively. Furthermore, 26.34% prefer carbohydrates; and 44.15 prefer soft drinks. 63.66% and 58.05% didn’t prefer vegetables and fruits respectively. Conclusions: It was concluded that prevalence of overweight and obesity showed moderate to high frequency among adults, and showed relationship was age, gender, marital status, tobacco smoking, dietary habits, and social habits. Thus effective educational, behavioral and social strategies are needed to prevent and control overweight and obesity in the population. Keywords: Prevalence, Determinants, Developing, Adults, Obesity, Overweight, Pakistan